CXCL8 in Tumor Biology and Its Implications for Clinical Translation - Xiong, Xingyu; Liao, Xinyang; Qiu, Shi; Xu, Hang; Zhang, Shiyu; Wang, Sheng; Ai, Jianzhong; Yang, Lu (Frontiers in Molecular Biosciences, 2022)
The chemokine CXCL8 has been found to play an important role in tumor progression in recent years. CXCL8 activates multiple intracellular signaling pathways by binding to its receptors (CXCR1/2), and plays dual pro-tumorigenic roles in the tumor microenvironment (TME) including directly promoting tumor survival and affecting components of TME to indirectly facilitate tumor progression, which include facilitating tumor cell proliferation and epithelial-to-mesenchymal transition (EMT), pro-angiogenesis, and inhibit anti-tumor immunity. More recently, clinical trials indicate that CXCL8 can act as an independently predictive biomarker in patients receiving immune checkpoint inhibitions (ICIs) therapy. Preclinical studies also suggest that combined CXCL8 blockade and ICIs therapy can enhance the anti-tumor efficacy, and several clinical trials are being conducted to evaluate this therapy modality.